Development and psychometric testing of a tool to measure missed nursing care - Kalisch, Beatrice J; Williams, Reg Arthur (The Journal of nursing administration, 2009)
In a qualitative study, medical-surgical and intensive care staff nurses reported that they did not complete a significant amount of nursing care on regular basis. Thus, it was determined that a quantitative tool was needed to measure the amount and type of missed nursing care and the reasons for missing care. The authors report the results of a psychometric evaluation of this tool (The Missed Nursing Care Survey [MISSCARE Survey]) to measure missed nursing care (part A) and the reasons for missed nursing care (part B). Two studies were conducted--study 1 (n = 459) and study 2 (n = 639). A sample of staff nurses was drawn from 35 medical-surgical, rehabilitation, and intensive care patient units in 4 acute care hospitals. Acceptability was high, with 85% of the respondents answering all items on the survey. Factor analysis with Varimax rotation resulted in a 3-factor solution for part 2 (communication, labor resources, and material resources). Cronbach alpha values ranged from 0.64 to 0.86. Confirmatory factor analysis demonstrated a good fit of the data. Using a contrasting group approach, a comparison of nurse's perceptions of missed care on intensive care units versus rehabilitation units resulted, as hypothesized, in a significantly lower amount of missed care on intensive care units. Pearson correlation coefficient on a test-retest of the same subjects yielded a value of 0.87 on part A and 0.86 on part B. Although further validation of the MISSCARE Survey is needed, current evidence demonstrates that the tool meets stringent psychometric standards.